ANALISIS PENERAPAN BLUE OCEAN STRATEGY (BOS) PADA UMKM KERAJINAN TANGAN TINS CROCHET - Aristami, Noery (Fakultas Ekonomi UNIBBA, 2025)
This research explores the application of Blue Ocean Strategy (BOS) in the context of a small and medium enterprise (SME) specializing in handmade crafts, particularly crocheted products. The Blue Ocean Strategy offers a way for businesses to create unique and innovative products, thereby avoiding direct competition in saturated markets. By focusing on differentiation and value innovation, businesses can expand their market space, attract new customers, and significantly boost sales and revenue. This research highlights how Blue Ocean Strategy is particularly advantageous for SMEs, such as Tins Crochet, that are facing intense price competition in the handmade craft sector. The primary goal of this study is to examine the implementation of BOS to create unique products, enhance customer satisfaction, and improve market positioning. This qualitative research uses a descriptive approach, with data collected through observation, interviews, and documentation. It focuses on the potential for innovation in handmade crochet products and how this can lead to market expansion. Findings suggest that Tins Crochet can apply BOS by developing innovative products like matching crochet bags and shoes, which cater to customers seeking coordinated fashion accessories. Additionally, the study analyzes the key elements of BOS—eliminate, reduce, raise, and create—applied to Tins Crochet’s operations. The company can reduce time constraints by offering flexible delivery timelines, eliminate the perception of overpriced goods by emphasizing product quality, raise the quality of materials used, and create innovative products that resonate with customer preferences. The research also addresses the competitive challenges the company faces, particularly with increasing global competition and the need to maintain uniqueness in the market. By adopting BOS, Tins Crochet can position itself strategically, focusing on high-quality, innovative products that appeal to niche markets, ultimately enhancing customer loyalty and expanding its business. This study underscores the importance of adopting Blue Ocean Strategy for businesses seeking sustainable growth and success in a competitive landscape.